2001
DOI: 10.3818/jrp.3.1.2001.115
|View full text |Cite
|
Sign up to set email alerts
|

The Predispositional Status of Violent Youthful Offenders: Is There a “Custody Gap” in Adult Criminal Court?

Abstract: This study focused on the immediate justice system response to violent youths in juvenile versus adult court. We examined 557 violent young offenders from Pennsylvania, of whom 138 were judicially waived to adult court and 419 were retained in juvenile court. Statistical analyses revealed that the transferred youths were more likely to be released from secure custody prior to a final disposition of their charges. Of those offenders who were released, the transferred youths also were more likely to recidivate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
(104 reference statements)
1
7
0
Order By: Relevance
“…The results of the current study fail to support this contention. Furthermore, these findings correspond well with those of other recent studies (Bishop et al, 1996;Fagan, 1995;Podkopacz & Feld, 1996;Winner et al, 1997; see also Myers 2001;Myers & Kiehl, 2001) that compared the recidivism of transferred juveniles with that of similar youths retained in juvenile court.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study fail to support this contention. Furthermore, these findings correspond well with those of other recent studies (Bishop et al, 1996;Fagan, 1995;Podkopacz & Feld, 1996;Winner et al, 1997; see also Myers 2001;Myers & Kiehl, 2001) that compared the recidivism of transferred juveniles with that of similar youths retained in juvenile court.…”
Section: Discussionsupporting
confidence: 91%
“…2. The following discussion of modern juvenile justice legislative changes in Pennsylvania and the data employed in this study have been previously presented elsewhere (Myers, 2001;Myers & Kiehl, 2001).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents of transferring juveniles to adult court generally emphasize two perceived advantages with this approach: stronger punishment and greater public safety. Although the waived offenders in this study initially were more likely to be released from predis-Myers / ADULT CRIME, ADULT TIME 187 positional secure custody than were the youth retained in juvenile court (see also Myers, 2001;Myers & Kiehl, 2001), the subsequent treatment received by the offenders in adult court was consistently of a harsher nature. The transferred juveniles were more likely to be convicted, and of those who were convicted, youth in adult court were more likely to be convicted of a targeted offense of robbery or aggravated assault.…”
Section: Discussionmentioning
confidence: 77%
“…Although these offenders may (or may not) undergo strict parole supervision, a central issue is whether the somewhat short-term incapacitative benefit achieved through juvenile transfer is offset by further criminal behavior once waived youth are released from confinement. In fact, recent research shows this to be the case as various studies have found greater, more serious, and faster recidivism on the part of waived youth as compared to similar offenders retained in the juvenile system (Bishop et al, 1996;Fagan, 1995;Myers, 2001Myers, , 2003bMyers & Kiehl, 2001;Podkopacz & Feld, 1996;Winner, Lanza-Kaduce, Bishop, & Frazier, 1997).…”
Section: Discussionmentioning
confidence: 99%